Post-Consumer Recycling of Polymers for Sustainable 3D Printing Filament Material - Siti Mutia Mawaddah; Mochamad Chalid; Sandrina Aras Maulidina; Cut Kayla Ashanti; Adam Febriyanto Nugraha (BRIN Publishing (Penerbit BRIN), 2023)
3D printing technology is rapidly developing in the manufacturing industry in producing complex and easily adjustable three-dimensional objects using the help of controls from computers. Behind its advantages, the 3D printing process requires filaments from virgin polymers which generally have a high price and adversely affect the environment. Post-consumer polymer recycling is a substitute material solution from virgin polymers and is environmentally friendly so as to support the realization of a circular economy. Studies on 3D printing filaments from post-consumer polymers have been discussed in this article, especially for filaments derived from acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), and polyethylene terephthalate (PET). In addition, this article also reviews the sources of recycled raw materials, difficulties during the process, mechanical properties, thermal properties and efforts to improve the quality of 3D printing products. The results show that recycling post-consumer polymers for 3D printing filament applications is a promising approach to reducing the environmental impact of 3D printing while still retaining the mechanical properties and printability of filaments. This article provides insight into several studies that address the development of 3D printing using post-consumer polymer materials.